2013
DOI: 10.1177/0300985813476058
|View full text |Cite
|
Sign up to set email alerts
|

Brain Lesions Associated WithClostridium perfringensType D Epsilon Toxin in a Holstein Heifer Calf

Abstract: A 6-month-old dairy heifer calf with no premonitory signs was acutely down after the morning feeding and could not rise. On presentation, the heifer was in right lateral recumbency and moribund with opisthotonus and left hind limb paddling. Following euthanasia, gross examination of the brain revealed multifocal loss of gray-white matter distinction and extensive petechiae throughout the brainstem. On histopathological examination, there was striking white matter edema and marked perivascular proteinaceous ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…In contrast, C. perfringens type D causes CNS pathology without diarrhea or pathological changes in the gut and is considered a true enterotoxemia (41). For example, in a detailed necropsy of a calf that succumbed to C. perfringens type D white matter disease, the entire length of the digestive system from esophagus to rectum was normal (17). In mice, the toxin can be absorbed from any segment of gut other than stomach (42) and does not cause diarrhea but in fact slows intestinal motility (14).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, C. perfringens type D causes CNS pathology without diarrhea or pathological changes in the gut and is considered a true enterotoxemia (41). For example, in a detailed necropsy of a calf that succumbed to C. perfringens type D white matter disease, the entire length of the digestive system from esophagus to rectum was normal (17). In mice, the toxin can be absorbed from any segment of gut other than stomach (42) and does not cause diarrhea but in fact slows intestinal motility (14).…”
Section: Discussionmentioning
confidence: 99%
“…In response to vitamin D supplementation, only MS patients who did not undergo glatiramer acetate treatment showed an increase in the number of Akkermansia , Faecalibacterium, and Coprococcus . It was recently discovered that intestinal colonization by the Clostridium perfringens type B is associated with relapse in MS. Toxins produced by C. perfringens can lead to microvascular complications leading to neuronal and oligodendrocyte damage [104107], which may serve as a trigger for future demyelinating events in susceptible individuals. Jhangi et al [108] compared MS patients with healthy subjects and observed increased concentrations of Archaea ( Methanobrevibacter ) and decreased concentrations of Butyricimonas and Lachnospiraceae in MS patients.…”
Section: Main Textmentioning
confidence: 99%
“…The histotoxic group includes diseases such as blackleg (Clostridium chauvoei), malignant edema (Clostridium novyi type A, Clostridium perfringens type A, Clostridium sordelli, Clostridium septicum), and bacillary hemoglobinuria (Clostridium haemolyticum). The group of enteric diseases includes several types of necrotizing and hemorrhagic enteritis (Clostridium difficile in calves, C. perfringens type C, C. perfringens type E) and enterotoxemia (C. perfringens type D) which occurs in small ruminants and possibly in cattle (Uzal et al 2002, Lobato et al 2006, Filho et al 2009, Mete et al 2013.…”
Section: Introductionmentioning
confidence: 99%